Prevalence and Risk Factors for Intestinal Protozoan Infections with Cryptosporidium, Giardia, Blastocystis and Dientamoeba among Schoolchildren in Tripoli, Lebanon. - Marwan Osman; Dima El Safadi; Amandine Cian; Sadia Benamrouz; Céline Nourrisson; Philippe Poirier; Bruno Pereira; Romy Razakandrainibe; Anthony Pinon; Céline Lambert; Ivan Wawrzyniak; Fouad Dabboussi; et al. (PLoS Neglected Tropical Diseases, 2016)
Background Intestinal protozoan infections are confirmed as major causes of diarrhea, particularly in children, and represent a significant, but often neglected, threat to public health. No recent data were available in Lebanon concerning the molecular epidemiology of protozoan infections in children, a vulnerable population at high risk of infection. Methodology and principal findings In order to improve our understanding of the epidemiology of intestinal pathogenic protozoa, a cross-sectional study was conducted in a general pediatric population including both symptomatic and asymptomatic subjects. After obtaining informed consent from the parents or legal guardians, stool samples were collected in January 2013 from 249 children in 2 schools in Tripoli, Lebanon. Information obtained from a standard questionnaire included demographic characteristics, current symptoms, socioeconomic status, source of drinking water, and personal hygiene habits. After fecal examination by both microscopy and molecular tools, the overall prevalence of parasitic infections was recorded as 85%. Blastocystis spp. presented the highest infection rate (63%), followed by Dientamoeba fragilis (60.6%), Giardia duodenalis (28.5%) and Cryptosporidium spp. (10.4%). PCR was also performed to identify species and genotypes of Cryptosporidium, subtypes of Blastocystis, and assemblages of Giardia. Statistical analysis using a logistic regression model showed that contact with family members presenting gastrointestinal disorders was the primary risk factor for transmission of these protozoa. Conclusions This is the first study performed in Lebanon reporting the prevalence and the clinical and molecular epidemiological data associated with intestinal protozoan infections among schoolchildren in Tripoli. A high prevalence of protozoan parasites was found, with Blastocystis spp. being the most predominant protozoans. Although only 50% of children reported digestive symptoms, asymptomatic infection was observed, and these children may act as unidentified carriers. This survey provides necessary information for designing prevention and control strategies to reduce the burden of these protozoan infections, especially in children.